Nodular Lymphocyte-Predominant Hodgkin Lymphoma: Review of Current Literature and Case Discussion. (July 2022) - Sidda, Adarsh; Naleid, Nikolas Kristopher; Manu, Gurusidda; Graffeo, Vincent; Jamil, Muhammad Omer
Nodular lymphocyte-predominant Hodgkin lymphoma (NLPHL) is a rare subset of Hodgkin lymphoma (HL). It has a distinct clinical and pathological presentation. Unlike classic HL, where the predominant malignant cells are Reed Sternberg cells, the malignant cells in NLPHL are known as lymphocyte predominant (LP) cells, with their own unique immunohistochemistry antigen expression and staining pattern. Based on risk stratification and staging of the disease, treatment can range from active surveillance in asymptomatic patients with no organ compromise or bulky disease, to aggressive chemotherapeutic agents in advanced disease. Guidelines on which of these chemotherapy regimens would offer the most benefit to our patients are limited due to lack of randomized-controlled studies. Majority of the current prospective data on treatment were inclusive of both HL and NLPHL. Thus, the regimens employed in treatment of NLPHL are similar to the ones used in HL, though NLPHL is often viewed as its own distinct entity. This article aims to review the current literature and future advances on treatment of this rare disease.